2019
DOI: 10.1111/acem.13726
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Emergency Department Patients and Association With Health Care Utilization

Abstract: Background: Depression is one of the most common illnesses in the United States, with increased prevalence among people with lower socioeconomic status and chronic mental illness who often seek care in the emergency department (ED). We sought to estimate the rate and severity of major depressive disorder (MDD) in a nonpsychiatric ED population and its association with subsequent ED visits and hospitalizations.Methods: This prospective cohort study enrolled a convenience sample of English-speaking adults presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 73 publications
5
44
1
Order By: Relevance
“…Basic characteristics are described in Table 1. [11,12]. However, we must point out methodologic differences between their studies [11,12] and ours.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…Basic characteristics are described in Table 1. [11,12]. However, we must point out methodologic differences between their studies [11,12] and ours.…”
Section: Resultsmentioning
confidence: 63%
“…[11,12]. However, we must point out methodologic differences between their studies [11,12] and ours. Whereas we used NHAMCS data on ED patients' depression status, these studies [11,12] relied on self-reported depression questionnaires administered to patients in their ED.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…The self-administered 9-item Patient Health Questionnaire (PHQ-9) is such an instrument; it is aligned with the DSM-5 symptom criteria for MDD and has been validated as a useful tool for the diagnosis of MDD and as a reliable and valid measure of depression symptom severity by a multitude of studies [11][12][13]. The PHQ-9 total score ranges from 0 to 27 and levels of depression symptom severity are typically categorized as the following: none/minimal (0-4), mild (5)(6)(7)(8)(9), moderate (10)(11)(12)(13)(14), moderately severe (15)(16)(17)(18)(19) and severe (20)(21)(22)(23)(24)(25)(26)(27) [11]. In 2016, the US Preventive Services Task Force (USPSTF) recommended routine screening for depression among adults in the US and the PHQ-9 as a suggested instrument [14].…”
Section: Introductionmentioning
confidence: 99%
“…A better understanding of the impact of depression symptom severity on future use of healthcare resources, speci cally that provided by hospitals, may be helpful to better determine the most appropriate targeted interventions that can be implemented earlier in the course of onset of worsening depression symptoms. A few small-scale studies conducted in the US have found depression severity to impact use of healthcare resources, including hospital encounters and mental health services [19,20]. Adekkanattu et al recently developed a natural language processing (NLP) method to extract PHQ-9 scores from unstructured data in electronic health records (EHRs) that exhibited high accuracy (97%) and sensitivity (98%) compared to a reference standard to identify patients with MDD and had utility for stratifying patients by depression severity [21].…”
Section: Introductionmentioning
confidence: 99%